Enhanced Protective System For Children In School Transportation - et. al., Manoharan. S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The higher number of vehicles on the roads increase in the number of road accidents worldwide. And these problems are considered as major public safety problem. A major part of providing a quality education to every children is ensuring their safety during transportation from their home to school. Thus, we have developed a smart and effective school bus system for the safety of children while transportation. This paper discusses about the hardware-based smart and effective school bus system for ensuring and monitoring the safety of school-going children through school bus. In this project, vehicles are considered as the main key enabling technology to improve children safety and the emergence of next-generation cooperative intelligent transport systems (ITS). In ITS, network services and applications (e.g., safety messages) will require event location information. Faster and efficient routing protocols could play a vital role in the applications of ITS, safe guarding both the driver and the children and thus maintaining a safe on-road environment. In this project, an intelligent transportation system (ITS) is designed to monitor real evacuation tests where an emergency event has been simulated and experimented and a general methodology is reported with the description of the main models and procedures. Models are calibrated and validated employing observed data obtained from ITS.